A review on legal interpretation of khalwat under the Syariah criminal law in Malaysia - Badarulzaman, Muhammad Hafiz; Azhar, Alias; Hussain, Mohammad Azam; Abdullah, Shuhairimi; Mohd Noor, Fauziah (2016)
Khalwat is one of Syariah criminal offences that is prescribed under Syariah criminal offence enactments in Malaysia.The issue before hand is that there are distintive definitions given by the Islamic jurist as well as definitons laid down in Syariah legislations of Malaysia.This article aims to discuss the definition of khalwat according to Islamic perspective in which it is not in pari materia with the interpretations from the state enactments in Malaysia.Furthermore, the discussion will be based on the category of khalwat that profounded from the Al Quran and Al-Hadith. This discussion also will be focusing more on the various interpretation of khalwat according to state enactments of Malaysia.This article uses the library research method in analyzing the documents such as books, articles and legal provisions in the Syariah criminal offence enactments of Malaysia. The study found that there are differences in khalwat interpretation in the legal provision of the Syariah criminal enactments of Malaysia.Despite the differences in the interpretation, khalwat could still be regarded as a bona fide Shariah criminal offence in Malaysia.